Clinical, radiological, and electroencephalographic features of HHV-6 encephalitis following hematopoietic stem cell transplantation. (December 2020) - Yassin, Ahmed; Al-Mistarehi, Abdel-Hameed; El-Salem, Khalid; Momani, Aiman; Al Qawasmeh, Majdi; Rodriguez, Rafael; Tummala, Sudhakar
Abstract: Background: To study the clinical, radiological, electroencephalographic, and cerebrospinal fluid (CSF) features of Human Herpes Virus 6 (HHV-6) encephalitis in leukemia patients underwent allogeneic hematopoietic stem cell transplantation (HSCT). Methods: We retrospectively reviewed all leukemia patients who underwent allogeneic HSCT between January 2010 and December 2018. The clinical, radiological, electroencephalographic, and CSF features of those with HHV6 encephalitis were recorded. Results: A total of five cases of HHV6 encephalitis were identified. Three patients had Chronic Myelogenous Leukemia, one had Chronic Lymphocytic Leukemia and one had Acute Lymphoblastic Leukemia. All of them presented a few months after transplantation with altered mental status. Comorbidities included pancytopenia, sepsis, graft versus host disease, and multi-organ failure. EEG showed focal seizures originating from temporal lobes in two patients, generalized or focal periodic discharges in three patients, focal slowing in two patients, and diffuse slowing in three patients. MRI brain showed T2/FLAIR hyper-intensities in four patients; two of them in bilateral temporal lobes, one in the thalamus/hypothalamus/brainstem/cerebellum/basal ganglia, and one in the periventricular areas. CSF showed pleocytosis, high protein, and positive HHV-6 PCR. Foscarnet was used as an anti-viral agent. Anti-epileptics used were phenytoin, levetiracetam, and valproic acid. Four patients died in a few months, whereas one recovered completely. Conclusions: HHV-6 encephalitis can add significant morbidity and mortality to leukemic patients following allogeneic HSCT. Patients present with typical clinical features of encephalitis. Salient EEG characteristics include periodic discharges or overt temporal lobe seizures. MRI findings are T2/FLAIR signal hyperintensities, mainly in the temporal lobes. Highlights: HHV-6 encephalitis is a fatal complication of allogeneic hematopoietic stem cell transplantation (HSCT). Common features include confusion, fever, headache, and seizures. EEG can show focal or generalized periodic discharges or overt temporal lobe seizures. MRI may show temporal lobe hyperintensities and diffusion restriction. Starting Foscarnet and antiepileptic drugs as early as post HSCT patients develop confusion is recommended.